Developing shoulder-over-shoulder rotation in the serve - Longo, E.; Peres Rodrigues, L. (Coaching and Sport Science Review, 2019)
Currently, high-level players have a tendency to perform serves with a strong vertical predominance. However, when looking at the basic technique of the execution of the serve, we notice that the movement is oriented horizontally forwards, with strong presence of trunk rotation in the longitudinal axis (twist). A crucial step in the development of the service is the transition from horizontal (twist) movement to the vertical. The objective of this article is to suggest exercises that help the transition from basic to more vertical mechanics.